Accessibility in Tourism: the accessibility of deaf people to the tourist services of Goiânia – GO - Silva, Maxmillian (Revista Turismo em Análise, 2013)
This article discusses the accessibility of deaf to the touristic services of the City of Goiânia - Estate of Goiás. Set up as a situation analysis, since is not limited to a specific case (as in a case study), but on the other hand, sees present data and information to enable an understanding of the situation through which passes the deaf in relation to tourism. To that, it employed a literature search in books, scientific articles and official sites, such as Ministry of Tourism and World Tourism Organization (WTO), and database, principally of Instituto Brasileiro de Geografia e Estatística (IBGE), and a field research (in Brazilian Sign Language) conducted with deaf attached to the: Primeira Igreja Batista de Goiânia; Sistema Educacional Chaplin; and Universidade Federal de Goiás. The research identified that there is touristic demand by deaf respondents and they show great interest for group travel. It was also possible to confirm the hypothesis that the greater difficulty of accessibility for the deaf is in communication, mainly the fact that most employees of touristic enterprises to be unaware of Brazilian Sign Language (Libras) or have it superficially.